y=e^x+3.
The given graph of the function y = e^x
he transformation occur when we add c to the parent function y = e^x giving us a vertical shift c unit in the same direction as the sign.
The y axis of a coordinate plane is the vertical axis. When a function shifts vertically, the value of y changes.
The given parent function: y = e^x,
we can now graph the vertical shift alongside i.e, c=3
Then, the upward shift function is, y = e^x + c
Substitute the value of c=3,
then, the transformed equation becomes, y = e^x + 3
as it goes through (0,4).
∴The equation y = e^x + 3 represents the transformed function.